Effect of Short-term-focused Training on a Phantom Model in Improving Operative Room Performance Among Surgical Residents: A Randomized Trial. Issue 2 (22nd April 2022) - Lingaraj, Chaitra; Rai, Sanjeet K.; Asuri, Krishna; Prajapati, Om P.; Kumar, Subodh; Bhattacharjee, Hemanga; Bansal, Virinder K.
Abstract : Background: Meta-analysis has shown the effectiveness of various training methods for the acquisition of laparoscopic skills in surgical training. However, there is very limited literature focusing on the translation of skill acquisition on training models into improved operating room (OR) performance. This study was conducted to evaluate the effectiveness of the Tuebingen trainer with integrated Porcine tissue in improving OR the performance of surgical trainees using standard assessment tools. Materials and Methods: The study was a single-blinded double-armed randomized control study conducted between July 2016 and March 2018. Eighteen, fourth, and fifth semesters of surgery residents were included in the study. The baseline performance was assessed in OR by performing laparoscopic cholecystectomy using validated scores, that is, Global Operative Assessment of Laparoscopic Skills (GOALS), Additional Five Criteria, Task-specific Checklist, Error Checklist, Visual Analogue Scale. The residents were then randomized into trainee and nontrainee groups. The training group received 5 days of short-term-focused training on the Tuebingen trainer, and the improvement was reassessed in OR. Results: The demographic profile of residents was similar. The baseline scores were comparable. The training group showed statistically significant improvement in GOALS (9.88±1.76 to 12±0.66, P =0.05 vs. 10.33±1.5 to 11.4±2.24, P =0.28), task-specific checklist (42.22±10.92 to 53.33±14.14, P =0.027 vs. 45.55±10.13 to 50±17.32, P =0.51), and error checklist. The operating time significantly reduced (36.0±4.03 vs. 50.44±11.39, P =0.0025) following training. Conclusions: Our study concludes that the training on the Tuebingen trainer with integrated porcine organs results in a statistically significant improvement in the OR performance of surgical residents as compared with the nontrained residents, thereby indicating a transfer of skills from training to OR.